2007
DOI: 10.1111/j.1346-8138.2007.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Amnia for intractable skin ulcers with recessive dystrophic epidermolysis bullosa: Report of three cases

Abstract: Recessive dystrophic epidermolysis bullosa (RDEB) is a disease characterized by recurrent blistering and chronic ulceration of the skin. In these patients, recurrent blisters frequently result in intractable skin ulcers due to impaired wound healing caused by mutations in the type VII collagen gene and malnutrition as well as by increased collagenase activity. To evaluate the efficacy of amnia for intractable ulcers in RDEB, we treated RDEB patients with amnia. The amniotic membrane was simply placed on the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…20 In addition, pain has been reported as being substantially diminished after AM application. 21,22 The use of AMs in the treatment of chronic ulcers is well established in the literature. [23][24][25][26][27][28][29] In a pilot prospective study using AM grafting for venous leg ulcers, Mermet et al 30 reported a significant increase in granulation tissue (from 16% 6 24% at day 0 to 56% 6 33% at day 30) and a decrease in fibrinous slough (from 36% at day 0 to 16% at day 14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In addition, pain has been reported as being substantially diminished after AM application. 21,22 The use of AMs in the treatment of chronic ulcers is well established in the literature. [23][24][25][26][27][28][29] In a pilot prospective study using AM grafting for venous leg ulcers, Mermet et al 30 reported a significant increase in granulation tissue (from 16% 6 24% at day 0 to 56% 6 33% at day 30) and a decrease in fibrinous slough (from 36% at day 0 to 16% at day 14).…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study complete re-epithelialization was not observed in all applications. Hasegawa et al 22 repeated the AM preparation and application procedure once a week for 10 weeks as a way of enhancing the chances of re-epithelization. Islets of new skin within wound bed and spontaneous re-epithelialization was detected on day 7.…”
Section: Discussionmentioning
confidence: 99%
“…The AM has been used clinically to treat variable diseases such as non-healing skin ulcers, vaginal atresia, and severe ocular surface disease [9,35]. These can confirm its biocompatibility and safety.…”
Section: Discussionmentioning
confidence: 99%
“…AM can reduce inflammation, inhibit vascularization, combat infection, and limit postoperative adhesion [32]. It has been used to treat variable diseases such as non-healing skin ulcers, vaginal atresia, and severe ocular surface disease [9,35]. Moreover, it can serve as adjunctive tissue to reduce surgical adhesions in abdominal surgery and otolaryngologic surgery [25,29,36].…”
Section: Introductionmentioning
confidence: 99%
“…AM can reduce inflammation, inhibit vascularization, treat infection and limit postoperative adhesions. Therefore, AM has considerable use in the treatment of various diseases, such as non-healing skin ulcers, vaginal atresia, and some ocular diseases [44] . Using a rat model, Choi et al demonstrated that implantation of a human AM after laminectomy significantly reduces epidural fibrosis on macroscopic evaluation; the authors suggested the potential use of human AMs as an adhesion technique in clinical practice [45] .…”
Section: Amniotic Membrane (Am)mentioning
confidence: 99%